An ecological partition of the Atlantic Ocean and its adjacent seas. (April 2019) - Beaugrand, Gregory; Edwards, Martin; Hélaouët, Pierre
Highlights: In this work, we first determined pelagic habitats using a set of selected environmental variables such as temperature, bathymetry, light at the seabed, sea ice concentration, current velocity and salinity. We then partitioned the North Atlantic Ocean and its adjacent seas at spatial resolutions of 2° latitude × 2° longitude and 0.5° × 0.5° using biological data from the Continuous Plankton Recorder (CPR survey; 238 plankton species or taxa sampled between 1946 and 2015 and representing more than 60 million data points). Finally, we combined the three biogeographies together to propose a new ecological partition of the North Atlantic and its adjacent seas into Ecological Units (EUs) and ecoregions. The comparison of our partition with the biogeochemical biogeography proposed by Longhurst reveals substantial differences in the location and size of biomes and provinces, especially over the continental shelf. In particular, boundaries of three known biomes (i.e. westerlies, polar and continental shelves biomes) differ substantially from the global-scale classifications. Abstract: In the past, partitions of the global ocean have been commonly carried out using relatively few environmental or biological variables. Although such partitions are undoubtedly useful on a global scale, we show that, at a basin scale, the use of a large number of biological variables greatly improves the accuracy of a partition. We first determined pelagic habitats using a set of selected environmental variables such as temperature, bathymetry, light at the seabed, sea ice concentration, current velocity and salinity. We then partitioned the North Atlantic Ocean and its adjacent seas at spatial resolutions of 2° latitude × 2° longitude and 0.5° × 0.5° using biological data from the Continuous Plankton Recorder (CPR survey). We used a total of 238 plankton species or taxa sampled between 1946 and 2015 representing more than 60 million data points. Finally, we combined the three biogeographies together to propose a new ecological partition of the North Atlantic and its adjacent seas into Ecological Units (EUs) and ecoregions. The comparison of our partition with the biogeochemical biogeography proposed by Longhurst reveals substantial differences in the location and size of biomes and provinces, especially over the continental shelf. In particular, boundaries of three known biomes (i.e. westerlies, polar and continental shelves biomes) differ substantially from the global-scale classifications.